2009 3rd International Conference on Bioinformatics and Biomedical Engineering 2009
DOI: 10.1109/icbbe.2009.5162738
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enhanced UV-B Radiation on the Cell Mitosis of the Callus in Wheat

Abstract: In order to study effects of enhanced Ultraviolet-B ( 280nm-320nm) radiation on the cell mitosis, mature embryos of wheat as explant were cultured in the Murashige and Skoog (MS) medium with different concentration of 2,4-D and 6-BA . The results indicated the inducing rate of the mature embryos from wheat on the MS with 2, 4-D 1.0 mg/L was higher and the callus was better than on the other Culture medium. The chromosomal mutation and mitosis of the callus in wheat were studied under the condition of the enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Qi et al (2002) found that the activities of superoxide dismutase, ascorbate peroxidase and CAT decreased significantly and the concentration of MDA and the rate of electrolyte leakage increased rapidly under higher UV-B radiation levels. Han et al (2002) found that 'root-bending' phenomenon would be caused under the enhanced UV-B radiation when wheat seeds germination and 'partition-bundle' division would be happened in root-tip cells of wheat seedlings. The distribution of actin filaments in wheat cells was disordered during interphase; the actin filaments disintegrated into short fragments and randomly distributed in the periplasm during prophase, and the actin fragments would disappear in metaphase (Chen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al (2002) found that the activities of superoxide dismutase, ascorbate peroxidase and CAT decreased significantly and the concentration of MDA and the rate of electrolyte leakage increased rapidly under higher UV-B radiation levels. Han et al (2002) found that 'root-bending' phenomenon would be caused under the enhanced UV-B radiation when wheat seeds germination and 'partition-bundle' division would be happened in root-tip cells of wheat seedlings. The distribution of actin filaments in wheat cells was disordered during interphase; the actin filaments disintegrated into short fragments and randomly distributed in the periplasm during prophase, and the actin fragments would disappear in metaphase (Chen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…R. Han et al (2002) found that the enhanced UV-B radiation would cause "root-bending" phenomenon when wheat seeds germination and "partition-bundle" division in root-tip cells of wheat seedlings [28]. Cell wall-plasma membrane-cytoskeleton have formed continuum in plant cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that enhanced UV-B radiation could lead to some abnormal phenomenon in living organisms, such as bio-membrane damage, membrane surface charge reduction, membrane permeability enhancement, cell electrophoresis rate decline, chromosome morphology alteration and aberrant cell division [26]- [28]. R. Han et al (2002) found that the enhanced UV-B radiation would cause "root-bending" phenomenon when wheat seeds germination and "partition-bundle" division in root-tip cells of wheat seedlings [28].…”
Section: Discussionmentioning
confidence: 99%
“…As cytoskeleton reorganization was revealed mainly in vitro in protoplasts and other cell cultures, [21][22][23][24] we have obtained the complementary results on cells of Nicotiana tabacum BY-2 suspension culture expressing gfp-mbd (microtubule-binding domain of MAP4) as a suitable cell model for in vivo MTs visualization. 33 Since BY-2 cells are more resistant to UV-B exposure as compared with A. thaliana seedlings, the higher doses of UV-B (34, 81 and 135 kJ/m 2 ) were used.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…18,19 Cytoskeleton role in such UV-induced morphological changes as their driving force remains poorly investigated, since only a few articles are focused on the cytoskeleton reorganization in vitro as one of the events underlying UV-B-induced responses of plant cell. [21][22][23][24][25] It was shown recently that the interphase and mitotic MTs in epidermal and cortex cells of all primary root zones of Arabidopsis thaliana L. seedlings expressing gfp-map4 (microtubule-assosiated protein 4) were randomized, depolymerized and/or stabilized in dose-dependent manner after the UV-B exposure (13.6-68 kJ/m 2 ) in vivo that was accompanied by the cell swelling and excessive root hairs formation. 26 Our further experiments give additional evidences that plant MTs are involved in signal transduction under UV-B stress.…”
mentioning
confidence: 99%